2020
DOI: 10.1155/2020/1720949
|View full text |Cite
|
Sign up to set email alerts
|

A Traffic Flow Evolution Process toward Mixed Equilibrium with Multicriteria of Route Choice Behaviour

Abstract: Based on the price-quantity adjustment behaviour principle of disequilibrium theory, the route choices of travellers are also affected by a quantity signal known as traffic flow, while the route cost is considered as a price signal in economics. Considering the quantity signal’s effect among travellers, a new route comfort choice behaviour criterion and its corresponding equilibrium condition are established. The network travellers are classified into three groups according to their route choice behaviour: tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In the QUE state, the route surplus capacities of all used routes between each OD pair are equal to the maximum surplus capacity and greater than (or equal to) the other routes with no flows [51].…”
Section: Mixed Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…In the QUE state, the route surplus capacities of all used routes between each OD pair are equal to the maximum surplus capacity and greater than (or equal to) the other routes with no flows [51].…”
Section: Mixed Equilibriummentioning
confidence: 99%
“…We apply the route rapidity and comfort adjustment criteria stimulatingly to individual travel route selection behaviour, which means that individuals will comprehensively consider the route cost and the route surplus capacity to make a route decision. When applied to the traveller group, the aggregated effect is performed the way that some travellers choose the shortest route and some travellers choose the most comfortable route, as discussed in this study [51]. Specifically, travellers with route rapidity requirement are likely to choose the shortest route with the minimum route cost under the current traffic condition for their trips in the next day, and their traffic flow evolution process converges to the traditional UE state, while travellers with route comfort requirement are supposed to follow the route comfort behaviour criterion based on the current traffic condition, and their traffic flow evolves to a stable state, which is defined as QUE (quantity adjusting user equilibrium).…”
Section: Introductionmentioning
confidence: 99%
“…Qing Keyan [2] and others screened travel distance, employment attraction, slow moving environment and traveler characteristics as the main characteristic variables to conduct research on slow traffic distribution prediction from the perspective of slow travel generation and travel distribution. Based on the 2013 and 2019 highway toll data of Jinan metropolitan area, Jiang Yong [3] and others used the null model method to analyze the spatial distribution pattern of highway traffic flow and the influencing factors through the distance decay function, and the results showed that the distance decay coefficient of highway traffic flow in Jinan metropolitan area was significantly negatively and linearly correlated with four factors, namely, economic density, population density, Gross Domestic Product (GDP), and the population, and the degree of influence decreased in order. And the degree of influence decreases in order.…”
Section: Introductionmentioning
confidence: 99%